Isolation of bacteriophage using E. Coli ATCC-25922 and E3 strain from water samples around Bangladesh - Alam, Rayhana (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.